2011
DOI: 10.1007/s12105-011-0305-8
|View full text |Cite
|
Sign up to set email alerts
|

Parotid Gland Solitary Fibrous Tumor: A Case Report and Clinicopathologic Review of 22 Cases from the Literature

Abstract: Solitary fibrous tumors (SFTs) are rare tumors in the head and neck, and even more so in the parotid gland. The mass-like clinical presentation and histologic features result in frequent misclassification, resulting in inappropriate clinical management. There are only a few reported cases in the English literature. Twenty-one patients with parotid gland solitary fibrous tumor were compiled from the English literature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 32 publications
4
92
0
2
Order By: Relevance
“…NF in more usual locations is frequently incorrectly considered a malignant lesion due to its rapid growth, presence of a high cellularity, abundant mitotic figures, and capacity to be poorly circumscribed, and NF of the parotid gland is Other malignancies (dermatofibrosarcoma protuberans, myxofibrosarcoma, rhabdomyosarcoma, angiosarcoma) are rarely included in the histologic or cytologic differential diagnosis [11,16,18,22,23,27,28,30]. Needless to say, this is a broad reactive and neoplastic differential Fig.…”
Section: Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…NF in more usual locations is frequently incorrectly considered a malignant lesion due to its rapid growth, presence of a high cellularity, abundant mitotic figures, and capacity to be poorly circumscribed, and NF of the parotid gland is Other malignancies (dermatofibrosarcoma protuberans, myxofibrosarcoma, rhabdomyosarcoma, angiosarcoma) are rarely included in the histologic or cytologic differential diagnosis [11,16,18,22,23,27,28,30]. Needless to say, this is a broad reactive and neoplastic differential Fig.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…There is a lack of destructive growth with limited mitoses. The strong reaction with CD34 and bcl-2 would help with separation from NF [30]. Desmin and other smooth muscle markers are generally positive in smooth muscle tumors (leiomyoma or leiomyosarcoma).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Solitary fi brous tumour is another entity that seldom is encountered in the salivary glands. In 2012, Bauer and associates reported a clinicopathological review of the literature and found 22 cases of parotid solitary fi brous tumour [ 170 ]. Rosai -Dorfman disease , or sinus histiocytosis with massive lymphadenopathy, is a rare usually self-limiting disease.…”
Section: Sclerosing Polycystic Adenosis and Miscellaneous Lesionsmentioning
confidence: 99%
“…DISCUSSÃO Carcinossarcomas são tumores raros em mulheres, assim como em cadelas, e apresentam prognóstico ruim comparado aos outros tipos de carcinoma (Tokudome et al, 2005). As características deste tipo histológico são extremamente variáveis (Misdorp et al, 1973). Embora a origem celular e a patogênese dos carcinossarcomas ainda não estejam completamente esclarecidas, os autores divergem quanto ao tipo celular que origina o tumor (Tavassoli, 1992;Rosen, 2009).…”
Section: Materiais E Métodosunclassified
“…Embora a origem celular e a patogênese dos carcinossarcomas ainda não estejam completamente esclarecidas, os autores divergem quanto ao tipo celular que origina o tumor (Tavassoli, 1992;Rosen, 2009). A avaliação da expressão de determinadas proteínas podem auxiliar no diagnóstico diferencial, tais como p63, citoqueratinas, CD34 e CD31 (Bauer et., 2012). Sendo assim, foi realizado um estudo do perfil imuno-histoquímico dessas células, afim de que pudesse ser identificada a origem do tipo celular.…”
Section: Materiais E Métodosunclassified